Comparative sensitivity of different loop-mediated isothermal amplication (LAMP) primer sets for rapid detection of Philippine isolates of white spots syndrome virus (WSSV) in shrimps, peneaus monodon (Fabricius, 1798). - Fuego, Jhon Philip P.
White spot syndrome virus (WVSSV) is a globally devastating Paneid shrimp pathogen that can be detected through loop-mediated isothermal amplification (LAMP) assay. In this study, four diffrent primer sets, particularly, Caipang et al. (2012), Kono et. al. (2004), Jaroenram et. al. (2009) and Maralit et al. (2012) were tested for sensitivity. Intially, DNA extraction was carried out using Caipang et. al (2012) protocol. Then, the serial dilutions of 1 ul DNA ml-1 template to 20-10 were used in the LAMP assay at 63 degrees centigrade incubation for 1 hour and 90 degrees centigrade termination for two minutes. For direct visualization, ethidium bromide was used in the 2.0 percent agarose gel electrophoresis. Results showed that Jaroenram et. al. (2009) primer was the most sensitive, followed by Caipang et. al. (2012) and Kono et. al. (2004) consecutively for Philippine isolates of WSSV. This study provides information in selection of primer sets for WSSV detection of LAMP assay.